2006
DOI: 10.1007/s00401-006-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HLA-DR-positive microglia in schizophrenia reflects impaired cerebral lateralization

Abstract: Immunological alterations have been demonstrated in peripheral blood and cerebrospinal fluid of patients with schizophrenia, while previous postmortem studies have provided an inconsistent picture as to the role of microglia in the context of schizophrenia. Microglial activation is a sensitive indicator of changes in the CNS microenvironment, such as inflammatory and neurodegenerative processes. The aim of the present postmortem study was to examine HLA class II (HLA-DR) expression on microglia in brain region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(154 citation statements)
references
References 44 publications
3
148
0
3
Order By: Relevance
“…Postmortem evidence is growing: brain microglial activation has been suggested in postmortem and positron emission tomography studies using (R)-[11C]PK11195, a ligand that recognizes the translocator protein [44][45][46][47]. Other postmortem studies have found increased numbers and structural degenerative impairments of human leukocyte antigen-antigen D related+ microglia in schizophrenia [48][49][50]. There is also some evidence from schizophrenia animal models showing progressive microglial activation, increased inducible nitric oxide synthase expression, and oxidative/nitrosative stress markers in the offspring of rats exposed to the viral mimetic polyriboinosinicpolyribocytidylic acid during pregnancy, which are prevented by the administration of clozapine [51].…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem evidence is growing: brain microglial activation has been suggested in postmortem and positron emission tomography studies using (R)-[11C]PK11195, a ligand that recognizes the translocator protein [44][45][46][47]. Other postmortem studies have found increased numbers and structural degenerative impairments of human leukocyte antigen-antigen D related+ microglia in schizophrenia [48][49][50]. There is also some evidence from schizophrenia animal models showing progressive microglial activation, increased inducible nitric oxide synthase expression, and oxidative/nitrosative stress markers in the offspring of rats exposed to the viral mimetic polyriboinosinicpolyribocytidylic acid during pregnancy, which are prevented by the administration of clozapine [51].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, several postmortem brain studies indicate that activated microglia are involved in both schizophrenia (Steiner et al., 2006) and major depression (Bayer, Busleia, Havasb, & Falkaia, 1999; Steiner et al., 2011). In accordance with, microglial activation may be a common finding in the pathogenesis of both the psychiatric diseases.…”
Section: Introductionmentioning
confidence: 99%
“…There were no statistically significant changes in the numbers of HLA-DR-positive cells in the anterior cingulate cortex [30,[33][34][35], dorsolateral prefrontal cortex [28,33,34], hippocampus [31,33,34,36], mediodorsal thalamus [33,34] and dentate gyrus [34] from patients with schizophrenia. CD68-positive microglia were not altered in the mediodorsal thalamus [37] and dorsolateral prefrontal cortex [38] in patients with schizophrenia.…”
Section: Schizophreniamentioning
confidence: 99%
“…Recent postmortem studies reported that microgliosis, labeled by HLA-DR, was increased in two schizophrenic patients in the anterior cingulate cortex and mediodorsal nucleus of the thalamus; both of these patients, who had acute psychosis, committed suicide [34]. Additionally, microgliosis was observed in the dorsolateral prefrontal cortex and mediodorsal nucleus for suicide cases [33].…”
Section: Suicidalitymentioning
confidence: 99%
See 1 more Smart Citation